Farming and manufacturing: The tax consequences of conducting these activities simultaneously - Grotepass, Debora Anneke (Department of Finance and Tax, 2019)
Different tax rules apply to farming and manufacturing activities respectively, and it appears that the South African Revenue Service (SARS) applies an arbitrary practice in determining whether, and if so, at what point a farming operation needs to be distinguished from manufacturing activities. This dissertation explores how and when a taxpayer is required to distinguish between farming and manufacturing activities within the context of a single business i.e. when one form of 'trade’ comes to an end, and when another form of 'trade’ commences. The First Schedule to the Income Tax Act, 1962 (ITA), and paragraph 12, in particular, gives certain privileges to farmers that other taxpayers do not enjoy. Similar to this, taxpayers who are conducting manufacturing activities, or operations accepted and listed by SARS as a process of manufacture or similar process, enjoy advantageous allowances in respect of the write off of machinery and buildings. Thus, the point at which one activity ends and the next activity begins can have significant tax consequences. This dissertation argues that these consequences are too significant to be governed by arbitrary decisions. In conclusion it is shown that the ITA provides the wherewithal to enable the decisions to be made based on sound statutory principles. Where the wherewithal is not present, appropriate additions to the legislation are recommended. Examples from case law are also discussed from which general principles to be used in practice are developed.